Enlarged Iliopsoas Bursa Compressing the Femoral Nerve Resulting in Femoral Mononeuropathy and Denervation Edema - Kapil Shirodkar; Khushboo Pilania; Bhavin G. Jankharia; Rajesh Botchu (Indian Journal of Radiology and Imaging)
Iliopsoas bursitis, although not rare, may manifest clinically as a detectable mass in the groin area. This condition has the potential to apply pressure on the adjacent femoral neurovascular bundle, leading to isolated mononeuropathy.